Thermal analysis and IR-spectroscopic research into interaction between organosilicon compounds and nonmetallic materials - Merezhko, Nina; Zolotarova, Oksana; Shulga, Olga (Eastern-European Journal of Enterprise Technologies, 2017)
It is established that the treatment of carbonate and silicate nonmetallic materials with organosilicon compounds is accompanied by the occurrence of endothermic and exothermic effects. Exothermic effects are associated with the cleavage of radicals in the organosilicon compounds. It was found that the tuff impregnated with ethyl silicate hydrolyzate is characterized by a wider range of removal of radicals – С2Н5. This may be due to their more intense interaction as compared to other non-metallic materials. Occurrence of endothermic effects is caused by release of water, which formed as a result of interaction between nonmetallic materials and organosilicon compounds. The strength of bond between organosilicon compounds and non-metallic materials decreases in a series of sodium phenyl siliconate>potassium methyl siliconate>sodium ethyl siliconate. An interaction between siliconates of alkali metals and silicate non-metallic materials is characterized by a stronger bond than that in the case of carbonate materials. The total loss of mass of impregnated silicates is 5.4–10 % versus 26.1–30.3 % in carbonates. The data on IR spectroscopy of the impregnated nonmetallic materials also testify to the physical-chemical interaction between carbonates and silicates and organosilicon compounds. The fixation and interaction of siliconates in the composition of carbonates is evidenced by the occurrence on IR spectra of new bands at 2900–3000 cm–1 and an increase in the intensity of bands responsible for oscillations in the bonds between silicon and oxygen. The evidence of this is also an increase in adsorbed water and a decrease in the intensity of absorption bands characteristic of anion There is also an expansion in the range of bands responsible for the valence and deformational oscillations in the bonds between silicon and oxygen. There appear the bands that are caused by the deformational oscillations in the bond between C–H and adsorbed water. The indicated peculiarities allow us to conclude that in the structure of silicates and carbonates there occurs both a physical fixation and a chemical interaction between siliconates of potassium and sodium.